2021
DOI: 10.1186/s12199-021-00955-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic-induced physical inactivity: the necessity of updating the Global Action Plan on Physical Activity 2018-2030

Abstract: To prevent and reduce inactivity, the World Health Organization (WHO) designed a global plan called Global Action Plan on Physical Activity 2018–2030 (GAPPA) in 2017. In this plan and according to the state of physical activity in 2016, actions and goals were set. However, the world is facing a COVID-19 pandemic, which has affected various aspects of lifestyle, including physical activity. Some studies have shown that physical activity reduced during the pandemic. For this reason, the WHO should review the GAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 11 publications
(8 reference statements)
5
52
1
3
Order By: Relevance
“…These modifications in lifestyle are such a concern that a call to change the Global Action Plan on Physical Activity (GAPPA) 2018–2030 of the World Health Organization has been done, and probably the goals of the GAPPA will be revised [ 25 ].…”
Section: The Impact On Primary Cardiovascular Prevention Risk Factorsmentioning
confidence: 99%
“…These modifications in lifestyle are such a concern that a call to change the Global Action Plan on Physical Activity (GAPPA) 2018–2030 of the World Health Organization has been done, and probably the goals of the GAPPA will be revised [ 25 ].…”
Section: The Impact On Primary Cardiovascular Prevention Risk Factorsmentioning
confidence: 99%
“…It has been estimated that approximately 23% of the adult population around the world and, more worrying, approximately 81% of teenagers do not meet the WHO global recommended levels of PA [ 20 ]. Screen time is a significant contributing factor to this sedentary behavior, which has undoubtedly worsened during the COVID-19 pandemic, when confinement, mobility restrictions, social distance and telework have been implemented [ 29 ]. Physical inactivity is a serious public health problem, especially in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…It is not to be excluded that isolation measures related to the COVID-19 pandemic in our country, such as quarantines and physical distancing, have had an impact on people's opportunities for PA. Some studies have shown a significant reduction in PA engagement and a marked increase in sedentary behaviors compared to pre-pandemic levels (30,31). This can affect the overestimate of the prevalence of PI during the data-collection period; however, it can be useful for future studies comparing PA levels and the impact of the pandemic on this factor.…”
Section: Discussionmentioning
confidence: 99%